2009
DOI: 10.1109/tbme.2008.2002151
|View full text |Cite
|
Sign up to set email alerts
|

Single-Trial Evoked Brain Responses Modeled by Multivariate Matching Pursuit

Abstract: We present a new approach to the analysis of brain evoked electromagnetic potentials and fields. Multivariate version of the matching pursuit algorithm (MMP) performs an iterative, exhaustive search for waveforms, which optimally fit to signal structures, persistent in all the responses (trials) with the same time of occurrence, frequency, phase, and time width, but varying amplitude. The search is performed in a highly redundant time--frequency dictionary of Gabor functions, i.e., sines modulated by Gaussians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…However, the use of MMP to decompose single-sweep EPs is not new and has previously been validated to extract meaningful information from EPs obtained during auditory stimuli [13]. Furthermore, matching pursuit has been used in several previous studies on average EPs in pharmaco-EEG [27], analysis of somatosensory EPs [28], investigation of the brain's pain processing [29] and preprocessing to source localization [30] and demonstrated a clear link between Gabor atoms and the corresponding EP components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of MMP to decompose single-sweep EPs is not new and has previously been validated to extract meaningful information from EPs obtained during auditory stimuli [13]. Furthermore, matching pursuit has been used in several previous studies on average EPs in pharmaco-EEG [27], analysis of somatosensory EPs [28], investigation of the brain's pain processing [29] and preprocessing to source localization [30] and demonstrated a clear link between Gabor atoms and the corresponding EP components.…”
Section: Discussionmentioning
confidence: 99%
“…These features describe the morphology of the mean energy in all traces, which has advantages over alternative methods such as the wavelet transform. First, the decomposition is adapted to the dataset and hence only extracts features representing common waveforms reflecting pain-specific information [13]. Secondly, the decomposition does not require any a priori choice of the best matched filter for decomposition into a filter bank by either a finite impulse response filter or wavelet transform [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, the binary model reflects a quite naïve assumption, because we know that brain responses do not switch on and off but respond to events with bell-shaped deflections. In single trial analysis, typical ERP responses were shown to fit with Gabor functions [16]. Thus, to model a single ERP deflection, we define for the target event interval:…”
Section: Model Functions For Erpsmentioning
confidence: 99%
“…Six different basis matrices Ψ are used in this work, each based on a different set of dictionary functions. Firstly the Gabor dictionary, as used in [8], [13], is used. Functions in this dictionary are defined by Gaussian envelope sinusoidal pulses:…”
Section: A Dictionary Functionsmentioning
confidence: 99%